Is Stagflation the Norm? - Blair Fix (Economics from the Top Down, 2023)
As much of the world grapples with post-Covid price gouging, it seems like a good time to revisit our understanding of inflation. In this post, I'm going to test Jonathan Nitzan and Shimshon Bichler's `stagflation thesis'. The idea is that `stagflation' — economic stagnation combined with high inflation — is not some exogenous `market shock'. According to Nitzan and Bichler, stagflation is a business strategy — one of two main routes to profit. The first route to profit is for businesses to hold prices steady while they try to sell more stuff. The second route is to jack up prices. Since this latter option requires restricting the flow of resources (stuff that flows freely cannot be dear), Nitzan and Bichler reason that when inflation rears its head, it ought to come with economic stagnation. In other words, stagflation is the norm. If this stagflation thesis is correct, then inflation ought to correlate negatively with economic growth. Looking at the United States, Nitzan and Bichler find evidence that it does. Here, I broaden their stagflation research by looking at all countries in the World Bank's global development database. I find that both within and across countries, economic growth (measured in terms of energy use) tends to decline as inflation increases. So Nitzan and Bichler appear to be onto something. Over the last half century, stagflation is the general rule.
Keywords: P16; Q4; N1; 330; breadth; depth; energy; inflation; stagflation